2022
DOI: 10.1037/per0000502
|View full text |Cite
|
Sign up to set email alerts
|

Reconceptualization of borderline conditions through the lens of the alternative model of personality disorders.

Abstract: Borderline (BPD) and schizotypal personality disorder (SPD) were introduced in the Diagnostic and Statistical Manual of Mental Disorders, Third Edition (DSM-III). However, the clinical differentiation of the 2 diagnoses (e.g., psychotic-like features) was challenging for diagnostic classification and clinical management. With the introduction of the alternative model for personality disorders (AMPD) in DSM-5 Section III, a dimensional approach was proposed, which potentially holds promise for better future dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 52 publications
(74 reference statements)
0
10
1
Order By: Relevance
“…Some evidence exists on the link between BPD and ideas of reference: prevalence rates of BPD patients suffering from ideas of reference across studies ranged from 43% to 61.7%. These rates are lower than those found in STPD or comorbid STPD/BPD patients but still higher than in other PDs (Meisner et al, 2021;Zanarini et al, 2013). Yet, correlations between BPD and ideas of reference were overall weak in our sourcesranging from .08 (Hummelen et al, 2012) to .21 (with the total number of BPD symptoms; Widiger et al, 1986)and ideas of reference were suboptimal in predicting BPD diagnosis (Sens = .49; Spec = .64; PPV = .70; NPV = .42; Widiger et al, 1986).…”
Section: Ideas Of Referencecontrasting
confidence: 70%
See 3 more Smart Citations
“…Some evidence exists on the link between BPD and ideas of reference: prevalence rates of BPD patients suffering from ideas of reference across studies ranged from 43% to 61.7%. These rates are lower than those found in STPD or comorbid STPD/BPD patients but still higher than in other PDs (Meisner et al, 2021;Zanarini et al, 2013). Yet, correlations between BPD and ideas of reference were overall weak in our sourcesranging from .08 (Hummelen et al, 2012) to .21 (with the total number of BPD symptoms; Widiger et al, 1986)and ideas of reference were suboptimal in predicting BPD diagnosis (Sens = .49; Spec = .64; PPV = .70; NPV = .42; Widiger et al, 1986).…”
Section: Ideas Of Referencecontrasting
confidence: 70%
“…Consistently, levels of this dimension in STPD patients were higher than in conventional clinical cut-offs (Meisner et al, 2021). Two neuroimaging studies (Dickey et al, 2007;Nakamura et al, 2005) Yet, it has to be noted that correlations between STPD and doubts about others' intentions varied consistently across studies (r range = .19-.41; Bach et al, 2017;Falkum et al, 2009;Hummelen et al, 2012) and that some sources suggested only acceptable predictive power or prototypicality of doubts about others' intentions for the diagnosis of STPD (Hummelen et al, 2012;Livesley et al, 1987;Pfohl et al, 1986).…”
Section: Doubts About Others' Intentionsmentioning
confidence: 74%
See 2 more Smart Citations
“…This complex composition of Criterion B trait facets has largely been supported by meta-analytic evidence (Watters et al, 2019), whereas specific findings suggest that the portrayal of borderline PD could be further improved by including features of psychoticism (e.g., perceptual dysregulation) and detachment (e.g., suspiciousness). However, this insinuates that all of the five Criterion B domains may well apply to borderline PD (Bach, Sellbom, et al, 2016; Evans & Simms, 2018; Meisner et al, 2021; Sellbom et al, 2014). Thus, although most clinicians do not treat their patients at a diagnostic level (i.e., categorical diagnosis), but rather at a symptom level (i.e., individual problems), it seems obvious to use individual trait profiles when formulating individualized treatment for patients with borderline PD.…”
Section: Utility Of Ampd To Capture Clinically Informative Features O...mentioning
confidence: 99%